An expense and income tracking mobile app with OCR to import receipts intelligently - Jiao, Shaobo (Nanyang Technological University, 2023)
The appearance of expense and income tracking app helps people analyse their money flow and thus save money in their daily lives. This kind of mobile app assists people in recoding money flow amounts, categorizing money flows and generating useful statistical analysis. However, inputting inefficiency is often an obstacle preventing people from using the apps. Not being able to see details of some money flows is another drawback of existing money tracking apps. One typical scenario is of supermarket expenses. Instead of having a simple supermarket expense record with only an amount and a short description, it would be better if corresponding supermarket receipt is stored in the app for reference as well. With one step further, a user can simply open the camera and scan a receipt. The corresponding receipt and record will both be automatically created and stored in the app, with details extracted from the receipt photo intelligently. Additionally, allowing importing records from external files, such as Excel files, will greatly improve inputting efficiency as well. This Final Year Project recognizes the drawbacks of existing money tracking apps and develops an improved app with useful functions including managing expense and income records and receipts, generating statistical reports, exporting and import records via Excel files.